17 Year Old Female Patient with Systemic Lupus Erythematosus and Ulcerative Colitis - Rizky Amelia; Supriono Supriono (The Indonesian Society for Digestive Endoscopy, 2014)
Gastrointestinal manifestations are common in systemic lupus erythematosus (SLE). Although the relationshipbetween SLE with ulcerative colitis (UC) rarely obtained, SLE patients with gastrointestinal manifestations shouldpreferably be evaluated for the possibility of an inflammatory bowel disease (IBD). UC prognosis associatedwith SLE is usually good, whereas by proper diagnosis and management, the clinical output and a good life expectancy of patients will be obtainedA young female, 17 years old, who had previously been diagnosed with SLE for 5 years, came with complaintsof abdominal pain and chronic diarrhea. From the results of colonoscopy and biopsy of the intestinal mucosawas noted that in accordance with UC. After receiving treatment for 6 days, she no longer obtained complaintsof abdominal pain and diarrhea. Keywords: systemic lupus erythematosus, gastrointestinal, ulcerative colitis, inflammatory bowel disease ABSTRAKManifestasi gastrointestinal merupakan hal yang sering terjadi pada lupus eritematosus sistemik (LES).Meskipun hubungan antara LES dengan kolitis ulseratif (KU) jarang didapatkan, sebaiknya pada pasien LESdengan manifestasi gastrointestinal dilakukan evaluasi untuk kemungkinan adanya suatu penyakit inflamasiusus besar. Prognosis UC terkait LES biasanya baik, dimana dengan diagnosis dan penatalaksanaan yang tepatakan didapatkan keluaran klinis dan harapan hidup yang baik pada pasien.Seorang perempuan muda berusia 17 tahun yang sebelumnya telah terdiagnosa LES selama 5 tahun, datangdengan keluhan nyeri perut dan diare kronik. Dari hasil pemeriksaan kolonoskopi dan biopsi mukosa ususdidapatkan gambaran yang sesuai dengan KU. Setelah mendapat terapi selama 6 hari, tidak didapatkan lagi keluhan nyeri perut dan diare.Kata kunci: lupus eritematosus sistemik, gastrointestinal, colitis ulseratif, penyakit inflamasi usus besar